Physico-Chemical and Morphogenetic Characteristics of Petrogypsids - Sharma, Manoj Kumar; Joshi, D C; Sharma, A K (Annals of Arid Zone, 2016)
Physico-chemical and morphogenetic characteristics of the gypsiferous soils have been studied in the arid region of Rajasthan. Detailed survey of the gypsiferous area has been carried out to characterize the constraints for their sustainable management. The study site was located near village Kawas. 20 km .. south of Banner, where the Petrogypsids occur widely. Detailed soil s,l}rvey of the area revealed that the soils were pale brown (10 YR 6/3). fine sand to loamy Â·sand. weekly aggregated. moderate to highly calcareous (8-20%) and 30-50 cm deep underlain by a compact petrogypsic horizon. These are classified as coarse loamy, hyperthermic Petrogypsids. The soils have alkaline pH (7.7-8.2); and low to moderate EC (0.20-2.26 d Sm-I ). The organic carbon (0.1 Q5-0.175%) and available phosphorus contents (4-9 kg ha-I) were in low :!Â·,11~ges.whereas available potassium was in medium to high range (101-405 kg ha- ). Maximum water holding capacity ranged between 'If;)! 17 and 30% and the moisture equi valent ranged from 5.6 io 14.2%. The available water capacity was 27 mm per 30 cm depth, which was very low and just adequate to support plant cover only for fcw days. These soils were adequate in available Fe (3.3-7.3 mg kg-'), Mn (5.4-8.2 mg kg-I), Cu (0.76-1.4 mg kg-I) and Zn (1.8-3.2 mg kg-'). Zinc arid copper were significantly and negatively correlated with organic carbon (r = -0.571 and -0.452), whereas Cu was positively related with pH (r = 0.516). Available Fe and Mn were significantly and positively, related with available water (I' = 0.50 I and 0.562), whereas Mn was negatively related with organic carbon (I' = -569).